2018
DOI: 10.1152/ajpregu.00286.2017
|View full text |Cite
|
Sign up to set email alerts
|

CRRL269: a novel designer and renal-enhancing pGC-A peptide activator

Abstract: The natriuretic peptides (NPs) B-type NP (BNP) and urodilatin (URO) exert renal protective properties via the particulate guanylyl cyclase A receptor (pGC-A). As a potential renal-enhancing strategy, we engineered a novel designer peptide that we call CRRL269. CRRL269 was investigated in human cell lines and in normal canines to define potential cardiorenal enhancing actions. The mechanism of its cardiorenal selective properties was also investigated. In vitro NP receptor activity was quantified with guanosine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 37 publications
3
30
0
Order By: Relevance
“…In bovine adrenal glands and zona glomerulosa cells, ANP activates PDE2 and reduces aldosterone levels generated from adrenal cells and tissues [ 25 , 26 ]. In addition, evidence from animal studies and a human clinical trial clearly supports pGC-A activation in the inhibition of aldosterone levels in vivo [ 27 , 28 ]. Thus pGC-A/cGMP/PDE2 signaling is another pathway involved in promoting water/sodium excretion.…”
Section: Particulate Gc-a/cgmp In Sodium and Water Homeostasismentioning
confidence: 99%
See 2 more Smart Citations
“…In bovine adrenal glands and zona glomerulosa cells, ANP activates PDE2 and reduces aldosterone levels generated from adrenal cells and tissues [ 25 , 26 ]. In addition, evidence from animal studies and a human clinical trial clearly supports pGC-A activation in the inhibition of aldosterone levels in vivo [ 27 , 28 ]. Thus pGC-A/cGMP/PDE2 signaling is another pathway involved in promoting water/sodium excretion.…”
Section: Particulate Gc-a/cgmp In Sodium and Water Homeostasismentioning
confidence: 99%
“…Optimally, such activators would also possess less hypotensive properties, which has limited the therapeutic use of NPs such as BNP (i.e., nesiritide). Based on selective AA cassettes of BNP and URO, we designed a novel pGC-A activator, CRRL269 that possesses renal-selective properties [ 27 ] ( Figure 2 ). In vitro experiments demonstrated that CRRL269 generated enhanced cGMP in HEK293 cells overexpressing pGC-A receptors and in primary human renal proximal tubular cells compared to native BNP and URO ( Figure 3 ).…”
Section: Novel Designer Pgc-a Activator Crrl269mentioning
confidence: 99%
See 1 more Smart Citation
“…For GC-A as a target, the drugs Carperitide and Nesiritide have been approved for the treatment of congestive HF, and for the chimeric natriuretic peptide CD-NP, positive therapeutic effects in a clinical study have been reported [34,35]. Recently, a novel GC-A activator, CRRL269, was designed, which induces in in vivo experiments an enhanced diuresis, natriuresis, and an increased glomerular filtration rate in comparison with the native GC-A activators BNP and URO [36]. GC-B is the target for drugs in the development of a treatment of skeletal diseases [37].…”
Section: Introductionmentioning
confidence: 99%
“…Further, ANP has been shown to exhibit anti-inflammatory properties and tumor-associated immune response [54,55]. Moreover, the synthetic novel designer natriuretic peptides have provided the renal enhancing actions of these hormones over the naturally occurring molecules [56][57][58][59].…”
Section: Introductionmentioning
confidence: 99%